Study of risk, incidence and mortality associated with postoperative pulmonary complications using assess respiratory risk in surgical patients in catalonia score - Tilak, Kedar M.; Litake, Manjusha M.; Shingada, Krupa V. (International Surgery Journal, 2019)
Background: Postoperative pulmonary complications (PPCs) are one of the major complications that are seen in patients undergoing surgeries and are also a significant cause of increased duration of hospital stay and mortality. Owing to their high incidence the present study was done to assess the risk and incidence of PPCs using the assess respiratory risk in surgical patients in catalonia (ARISCAT) score and to observe the mortality related to PPCS. Methods: The study was done at a tertiary care center over a period of three month and 150 patients were involved. The patients were the categorized into three risk groups and were observed for development of any PPCs. Results: Out of the 150 patients that were studied, 29 developed some form of PPC. 21 out of these 29 (72.41%) patients were from the high-risk category. 11 out of the 29 patients died in a span of 30 days. Pneumonia was seen to be the most common PPC. Conclusions: ARISCAT score can be useful as a preoperative evaluation tool to classify patients into risk groups and predict the development of PPC in the high-risk groups and to take measures to reduce the risk of PPCs. We conclude from our study that anemia, emergency surgery and surgery with duration of more than 3 hours were significant factors contributing to both the incidence and mortality of PPCs irrespective of the risk group.